Comment légitimer l'accession au statut d'expert pour limiter les controverses : étude de cas en biodiversité - Daniel Marc; Frédéric Blanc (VertigO)
Environment in general, and even more so Wildlife management, are fields in which the need and the claim for expertise are both very strong and distributed. This is partly due to the intricate issues resulting from various scientific disciplines. The temptation to seek in science for an objective guaranty for the rightfulness of a public policy thus significant. This is also a field of high interest of the population and on which it is fairly easy to have an opinion. There are therefore ideal conditions for much controversy on the subject. The stumbling blocks are varied: from the definition of the expert, of the scientist, of the user, of the knowledgeable or the public to the legitimacy of the experts themselves. We show in this case study, the long-term strategies developed by two environmental actors in France, the « Office National de la Chasse et de la Faune Sauvage » and the « Conservatoires d’Espaces Naturels », to gain a greater legitimacy. The first disposes of a rational legal legitimacy and has wished to complete by developing a scientific expertise. The second, strong of their local acceptation and their rigorous practice, have seeked to legitimate their action through law. The two now seem to have succeeded. Their investment seems to have been productive from the point of view of their intrinsic legitimacy. This investment may be more subtle in view to the real repercussions of this legitimacy. Much controversy remains regardless of the expert’s legitimacy. The efficiency of the investments must thus be kept in perspective. However, it results in a professionalization of expert status, clearer and better supported, enabling to think that this proliferation of actors, source of competition is a chance of the general interest.